Fenofibrate, which reduces risk of sight‐threatening diabetic retinopathy in type 2 diabetes, is associated with early narrowing of retinal venules: a FIELD trial substudy. Issue 4 (13th April 2022) - Quinn, Nicola; Januszewski, Andrzej S.; Brazionis, Laima; O'Connell, Rachel; Aryal, Nanda; O'Day, Justin; Scott, Russell; Mitchell, Paul; Jenkins, Alicia J.; Keech, Anthony C.; ,
Abstract: Retinal vessel calibre metrics were evaluated at baseline and 2 years in a FIELD substudy ( n = 208). Central retinal venule calibre was significantly reduced by fenofibrate and unchanged by placebo. Arteriole metrics did not change. Larger studies relating retinal vessel calibre to future diabetes complications and response to therapy are merited.